Tracing of lithium supply and demand bottleneck in China’s new energy vehicle industry—Based on the chart of lithium flow - Zheng, Linchang; Chen, Ge; Liu, Litao; Hu, Yuqi (Frontiers in Energy Research, 2022)
With the rapid development of China’s new energy vehicle industry, the supply security of lithium resources is crucial. To ensure the healthy development of the new energy vehicle industry and the security of supply of key mineral resources, it is necessary to accurately determine the supply and demand pressure of lithium resources and their sources. This study analyzes the lithium stock and flow at the end of the new energy vehicle chain by constructing a material flow analysis framework for the new energy vehicle industry and compiling a lithium resource flow table for the new energy vehicle industry, and the results show that 1) the supply and demand pressure on lithium resources in China is increasing year by year, and the external dependence of lithium resources has reached 75% in 2019; 2) China’s domestic lithium battery production and consumption accounted for nearly 70% of the lithium consumption in various industries, of which 60% of the lithium batteries were assembled on new energy vehicles, and the net outflow of lithium exceeded more than the lithium consumption of new energy vehicles in 2019. The lithium consumption of new energy vehicles was more than five times that of the previous year. Insufficient supply of domestic lithium ore, lithium inventory, and import and export are the key reasons for the pressure on lithium supply and demand in the new energy vehicle industry; 3) By the end of 2019, the cumulative scrap lithium batteries in new energy vehicles contain about 10,000 tons. The lithium accumulated in new energy vehicles has 26,500 tons. These results provide a theoretical basis for policy recommendations to ensure the healthy development of the new energy vehicle industry and to promote international cooperation in the development, utilization, and recycling of lithium resources.